How positive peace might enhance the success and adequacy of climate change adaptation in the global south - Monyei, Emmanuel; Heintze, Hans-Joachim (Frontiers in Climate, 2025)
Climate change adaptation aims to reduce vulnerability to climate impacts across various sectors. Current adaptation efforts appear inadequate as they do not address deep-rooted structural barriers such as inequality, exclusion, and weak governance. This limitation hinders the long-term sustainability of these adaptation efforts. This systematic review draws on Johan Galtung’s concept of positive peace, which encompasses equity, justice, and inclusion. It seeks to explore how integrating these principles into adaptation efforts might enhance their effectiveness and sufficiency. The article employed a systematic literature review method based on the PRISMA approach to evaluate scholarly and policy-focused research on the intersection of positive peace and climate adaptation. Several databases were utilized, including Scopus and Web of Science. Searches used key terms such as ‘climate adaptation’ and ‘successful.’ The inclusion criteria emphasized studies addressing adaptation beyond mere technical solutions and those considering justice, governance, and long-term sustainability. Galtung’s peace framework served as an interpretive lens. The findings from this study indicate that while positive peace concepts are not always explicitly utilized in adaptation literature, core elements—such as distributive, procedural, and recognitional justice—often appear as critical to successful outcomes. Additionally, climate adaptation practices that intentionally incorporate these principles tend to be more resilient, community-driven, and responsive to climate risks. A grounded demonstration of this finding is illustrated with a case from the Solomon Islands, showing how integrating peacebuilding approaches into community-based adaptation may enhance both resilience and social cohesion. Consequently, the paper proposes a conceptual framework linking positive peace dimensions with the criteria of adaptation success and adequacy. Integrating positive peace into climate adaptation may offer a pathway for addressing systemic barriers, especially in non-conflict settings. Furthermore, it could redefine adaptation from reactive risk management to proactive justice-centered planning. However, more research is necessary, as beyond this systematic review and a few case studies, empirical evidence remains scarce. Adaptation activities are often undocumented or assessed without justice metrics. Although empirical testing is needed, the study underscores that integrating positive peace may help deliver more sustainable outcomes in highly vulnerable regions.